CTAB Reverse Micelles as Catalysts for the Oxidation of Ascorbic Acid by K3[Fe(CN)6] - K. Bhargavi; P. Shyamala; P S S Chakravarthi; K V Nagalakshmi (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
The oxidation of ascorbic acid by K3[Fe(CN)6] was studied in reverse micellar systems composed of CTAB (Cetyltrimethylammonium bromide), and it was found  the observed first order  (k1(aq) = 5.2×10−5 s−1, k1(rev) = 61.4×10−4 s−1) rate constant in reverse micellar medium is around forty times higher compared to aqueous medium under identical conditions. The rate enhancement (k2(aq) = 0.9×10−5 mole−1.dm3.sec−1, k2(rev) = 1.75×10−3 mole−1.dm3.sec−1)  is attributed to the large concentration effect and lower dielectric constant in the reverse micelles. The rate of the reaction increases with increase in W = {[H2O]/[surfactant]} which is explained in terms of ionic strength of the water pool. The effect of surfactant concentration on rate was explained on the basis of Berezin pseudo phase model. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).